2016
DOI: 10.1111/ggi.12767
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dementia on behavioral independence and disturbance

Abstract: Moderate correlations were found between severity of dementia and behavioral independence levels and frequencies of behavioral disturbances. There were both easier and harder to accomplish behaviors, and both higher and lower frequencies of behavioral disturbances. Geriatr Gerontol Int 2017; 17: 605-613.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Declining BPSD increase caregiver distress. In this study, the DBD score of all informal caregivers was higher than that reported in other studies of dementia patients . If patients had severe BPSD before KCN use and/or worsening BPSD after KCN use, their informal caregivers might continue to use the CHR, and their care managers may be more likely to attend collaborative meetings.…”
Section: Discussionmentioning
confidence: 99%
“…Declining BPSD increase caregiver distress. In this study, the DBD score of all informal caregivers was higher than that reported in other studies of dementia patients . If patients had severe BPSD before KCN use and/or worsening BPSD after KCN use, their informal caregivers might continue to use the CHR, and their care managers may be more likely to attend collaborative meetings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the 150 seconds of the SHAP total item score derived from the linear regression analysis [20] were compared for different component items (). The SHAP Abstract Object Tasks scores for Heavy Power, Light Spherical, and Heavy Spherical were low in a stepwise fashion, whereas those for Light Lateral, Light Tip, and Light Extension were high in a stepwise fashion.…”
Section: Resultsmentioning
confidence: 99%
“…In linear regression, more difficult items shift the line to the left and have a steeper slope, whereas easier items shift the line to the right and have a gentler slope. Moreover, to clarify the difficult items, predicted scores were calculated for each item using the time required to carry out the total item (150 seconds) in the linear regression function [20]. To assess the applicability of linear regression, the determination coefficient ( R 2 ) was used to compare each component item score that was obtained with the predicted values derived from the linear regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Executive functions have already been indicated to deteriorate prematurely in people with dementia, even starting from mild cognitive impairment [30] and may be the earliest symptom that accompanies cognitive decline, further affecting the ability to prepare meals and eat [31,32]. In fact, patients in advanced stages of dementia are often institutionalized due to increasing dependence.…”
Section: Discussionmentioning
confidence: 99%